2017
DOI: 10.1016/j.actaastro.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid SGP4 orbit propagator

Abstract: Two-Line Elements (TLEs) continue to be the sole public source of orbiter observations. The accuracy of TLE propagations through the Simplified General Perturbations-4 (SGP4) software decreases dramatically as the propagation horizon increases, and thus the period of validity of TLEs is very limited. As a result, TLEs are gradually becoming insufficient for the growing demands of Space Situational Awareness (SSA). We propose a technique, based on the hybrid propagation methodology, aimed at extending TLE valid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This work was closely followed by [55], in which the same method was applied, alongside a bias correction function. Similarly, other authors [56,57] have shown improvement of the SGP4 prediction using error correction functions, based on prediction error periodicity.…”
Section: Orbit Predictionmentioning
confidence: 67%
“…This work was closely followed by [55], in which the same method was applied, alongside a bias correction function. Similarly, other authors [56,57] have shown improvement of the SGP4 prediction using error correction functions, based on prediction error periodicity.…”
Section: Orbit Predictionmentioning
confidence: 67%
“…However, it is different from this study as it shows the opposite way. For example, a study by [9] shows that using more input features gave higher accuracy. However, they are using the Holt Winter, a tricky statistical technique that requires more input data.…”
Section: Resultsmentioning
confidence: 99%
“…The SGP models use average orbital elements, whose values are obtained using a special procedure for removing short-period variations [10]. SGP models have been developed over decades [17] and are now widely used [7,15].…”
Section: Introductionmentioning
confidence: 99%